Factores de riesgo de delirium en adultos mayores hospitalizados. - Pintado Ruiz, Alex Fabricio (Machala : Universidad Técnica de Machala, 2022)
Introduction: Delirium is an acute disorder of attention and cognition, known as an acute confusional state. In Latin America it affects more than 2.6 million each year in the United States, in regions of South America, such as Brazil in 47%, in Europe, low countries such as Holland in 16%, and at the level of Asia, Japan, studies report a prevalence of delirium that ranges between 16% and 19% of patients. Objective: To describe the risk factors for delirium in hospitalized older adults through the review of updated scientific articles, which provide guidelines for correct prevention. Methodology: This is a descriptive study, based on the systematic review of scientific articles in different databases such as: PUBMED, GOOGLE SCHOLAR, COCHRAINE, SCIELO of the last 5 years. Conclusion: Delirium is common in hospitalized older adults, with a prevalence of 1 to 2% in the community and 23% in hospitalized patients, this is attributed to its form of presentation that goes unnoticed or is confused with other disorders, diseases, in the In most cases, delirium is active hiccups, it represents 75% of older adult patients, it predominates in the intensive care area in 50 to 70% of cases, it is evident that through prevention with non-pharmacological approaches, delirium can be reduced among patients. hospitalized elderly patients by up to 54%.
Introducción: El delirium, es un trastorno agudo de la atención y la cognición, conocido como estado confusional agudo. En América latina afecta a más de 2,6 millones cada año en los Estados Unidos, en regiones de América del Sur, como Brasil en 47%, en Europa, países bajos como Holanda en el 16%, y a nivel de Asia, Japón, estudios informaron una prevalencia de delirio que oscila entre el 16% y el 19% de pacientes. Objetivo: Describir los factores de riesgo de delirium en adultos mayores hospitalizados a través de la revisión de artículos científicos actualizados, que faciliten las pautas para una correcta prevención. Metodología: Se trata de un Estudio descriptivo, basado en la revisión sistemática de artículos científicos en las diferentes bases de datos tales como: PUBMED, GOOGLE SCHOLAR, COCHRAINE, SCIELO de los últimos 5 años. Conclusión: El delirio es común en adultos mayores hospitalizados, con una prevalencia del 1 a 2 % en la comunidad y 23% en hospitalizados, esto se atribuye a su forma de presentación que pasa desapercibido o es confundido con otros trastornos, enfermedades, en la mayoría de casos el delirio es hipo activo representa el 75% de pacientes adultos mayores, predomina en el área de cuidados intensivos en 50 a 70 % de casos, se evidencia que mediante la prevención con enfoques no farmacológicos se pueden reducir los el delirio entre los pacientes de edad avanzada hospitalizados hasta en un 54 %.
Keywords: DELIRIUM; DETERIORO COGNITIVO; FACTORES DE RIESGO; ADULTOS MAYORES